The fixed wage puzzle why profit sharing is so hard to implement - Jerger, Jürgen 1965-; Michaelis, Jochen 1959- (Osteuropa-Inst., 2010)
It is well known that profit sharing arrangements Pareto-dominate fixed wage contracts. Share agreements are (far) less than ubiquitous, however. This paper offers a solution of this "fixed wage puzzle“ by adopting a perspective of bounded rationality. We show that share arrangements that fulfill "plausible“ constraints are not generally acceptable to both firms and unions.